GIS- Based oil palm estate management: adoption of internet of things (iot) to improved yield / Zamry Bunyau Sadi...[et.al] - Sadi, Zamry Bunyau; Ujang, Rudy; Jutim, Fiona Banun (2019)
Palm oil is the most traded vegetable oils in the world due to its characteristic which produced higher oil yield compare with soybean and rapeseed. Oil palm industry in Malaysia started in 1970 after being converted into commercial crops after rubber.